Evaluation of Neutralizing Antibodies against SARS-CoV-2 Variants after Infection and Vaccination Using a Multiplexed Surrogate Virus Neutralization Test. (9th January 2022) - Lynch, Kara L; Zhou, Shuxia; Kaul, Ravi; Walker, Roger; Wu, Alan H
Abstract: Background: The SARS-CoV-2 virus has mutated and evolved since the inception of the COVID-19 pandemic bringing into question the future effectiveness of current vaccines and antibody therapeutics. With evolution of the virus updated methods for the evaluation of the immune response in infected and vaccinated individuals are required to determine the durability of the immune response to SARS-CoV-2 variants. Methods: We developed a multiplexed surrogate virus neutralization test (plex-sVNT) that simultaneously measures the ability of antibodies in serum to inhibit binding between angiotensin converting enzyme-2 (ACE2) and 7 SARS-CoV-2 trimeric spike protein variants, including wild type, B.1.1.7(α), B.1.351(β), P.1(γ), B.1.617.2(δ), B.1.617.1(κ), and B.1.429(ε). The assay was validated against a plaque reduction neutralization test (PRNT). We evaluated 170 samples from 97 COVID-19 patients and 281 samples from 188 individuals that received the Pfizer-BioNTech or Moderna mRNA vaccines. Results: The plex-sVNT demonstrated >96% concordance with PRNT. Antibody neutralization activity was significantly reduced for all SARS-CoV-2 variants compared to wild type in both the infected and vaccinated cohorts. There was a decline in overall antibody neutralization activity, within both cohorts, out to 5 months post infection or vaccination, with the rate of decline being more significant for the vaccinated. Conclusions: The plex-sVNT provides a correlative measure to PRNT and a convenient approach for evaluating antibody neutralization against SARS-CoV-2 variants. Neutralization of SARS-CoV-2 variants is reduced compared to wild type and declines over the ensuing months after exposure or vaccination within each cohort, however it is still unknown what degree of neutralizing capacity is protective.